Submerged TLP-type mooring system analysis for a heaving buoy wave energy converter - Shi, H.; Tian, H.; Meng, X.; Wang, Xiangyu (2016)
A heaving buoy wave energy converter (HBWEC) with a hydraulic power take off is proved to be feasible at the a coastal area experiencing relatively small wave heights and short wave periods. The paper presents a hydrodynamic and comprehensive analysis methodology for a mooring system of the HBWEC, which is composed of a tension leg platform (TLP) type of submerged floating body (SFB) and tendons. The study is based on a 10KW HBWEC sea trial project. The additional dynamic damping is simulated to capture the coupling effects of the mechanical hydraulic resistance of the HBWEC on the mooring system. Classic multi-criteria decision making method called TOPSIS, is employed to investigate the optimum submerged position of the TLP floater. Research shows that the SFB position could achieve an optimal solution considering displacement response, tension and economic factors simultaneously.